Pendampingan Pelatihan Pendidikan Karakter Santri dan Jiwa Enterprenership Santri (Praktek Keterampilan Batik Jumput) di Pondok Pesantren Shofa Marwa - Hamdanah, Hamdanah; Faris Wijdan , Ahmad (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Shofa Marwa Islamic Boarding School is an Islamic educational institution that has various educational programs ranging from junior high school to vocational high school and diniyyah, but also some students who are currently studying at universities, both public universities such as Jember University and religious universities such as Islamic University. In carrying out community service, such as accompanying students at the Shofa Marwa Islamic Boarding School in Jember, it is hoped that students will be educated about the importance of character education, independence education, and entrepreneurship education. They must also know how to make jumput batik and package it beautifully to attract customers. This service is carried out in several stages, namely Lectures and Discussions and Demonstrations on how to make jumput batik. Mentoring and training for student independence and character education of students as well as training in making jumput batik, providing information and implementing training are very much felt by students because the administrators have the responsibility to disseminate it to all students so that all students are also able to apply and are able to make jumput batik, so that all students have a strong character and are able to be independent and are able to develop an entrepreneurial spirit. Community empowerment by providing assistance and training on the importance of character education and the importance of independence education and instilling an entrepreneurial spirit is very important, especially when accompanied by training on how to make batik jumput and direct practice in making batik, so that community service like this really needs to be continuously pursued as an effort to realize the Tri Dharma of Higher Education, to strengthen the community, the presence of academics is a necessity.